TRYPANOSOMA spp. in captive primates in a brazilian zoo - Jose dos Santos, Wesley; Maisa Guiraldi, Livia; dos Santos Paixão Marques, Mirian; Fernanda Alves-Martin, Maria; Pacheco Sanchez, Gabriela; Barbosa da Silva, Daniela; Bodelao Richini-Pereira, Virginia; Suemi Kurokawa, Cilmery; Baldini Lucheis, Simone (Revista de Patologia Tropical / Journal of Tropical Pathology, 2021)
Captive animals, despite the constant care provided, are susceptible to infections from different sources. We herein report the natural trypanosome infection of 11 (28.2% positive) out of 39 non-human primates from 13 different species, in a Brazilian zoological park. Immunofluorescent antibody test (IFAT) and conventional polymerase chain reaction (cPCR) ruled out Trypanosoma cruzi, the etiological agent of Chagas disease. However, sequencing performed with positive samples employing hsp70 primers revealed similarities from 86% to 88% to diverse trypanosomes, including T. cruzi, Trypanosoma grayi, Trypanosoma lewisi, Trypanosoma rangeli and Trypanosoma vivax. We believe that the low similarity values obtained by sequencing reflect the difficulties in the molecular identification of trypanosomes, which share a large portion of their genetic material; this similarity may also preclude the diagnosis of co-infection by more than one trypanosome species. Thus, our study demonstrates the presence of diverse trypanosomes in primates, which are susceptible to infection by these parasites. Mechanical devices such as windows and bed nets, etc., are required to avoid vector insects in these environments, in addition to preventive quarantining of animals recently introduced into zoos. Therefore, investigation of the parasites in both the animals already residing in the zoo and those being introduced is of paramount importance, although no easy task. KEY WORDS: Non-human primates; monkey; diagnosis; trypanosomes.